A formação do professor da educação infantil no contexto da modalidade a distância: o curso de pedagogia em foco - Pietrobon, Sandra Regina Gardacho (2018)
As general objective for the present study it is intended to analyze the theoretical and methodological inputs that were brought to the pedagogical practice of early childhood education teachers through a Pedagogy course study in the distance learning method from a public higher education institution in Parana. As a starting hypothesis, it was expected that the throughout the study possible methodological paths for the structuring of the pedagogical practice with children in the early childhood education were indicated, which leads those that are in training to a direction in their practices and to the inclusion of children as participants of the process. Therefore, a leading question has been elaborated to initiate the research stages: What theoretical and methodological contributions a distance learning Pedagogy course from a public higher education institution from Parana has brought to the pedagogical practice of teachers in the early childhood education? From this point of view, the study had a qualitative and quantitative perspective concerning the data collected by the application of an online survey with documental analyses of the pedagogical proposal of the researched course. The structuring of questions for the survey followed the Vieira parameters (2009). The subjects of the research were 137 former students from the distance learning Pedagogy course altogether, considering that the final sample was of 51 participants from different centers in the countryside of Parana (Lapa, Prudentópolis, Dois Vizinhos, Apucarana, Pato Branco, Laranjeiras do Sul). These egresses attended the first offer of the course from 2011 to 2014. The data analyses was based in the assumption that in the teacher`s practice there is a theory of the knowledge that guides their choices, knowledges and ways of practice. The collected data show that the course fulfilled the required training methodologically and theoretically in relation to early childhood education, however when it comes to the professional and disciplinary knowledges and expertise, gaps emerged from the contribution of the former students in formative terms, that comes out in the theoretical-practical relation, in the insufficient interaction concerning the development of supervised internships in the area, and in the methodologies and forms of assessment. For that matter, the hypothesis could be confirmed as there has been a preparation of the course for the pedagogical practice in the early childhood education stage. However it is suggested that the course might rethink its ways of interaction with the students in posterior offers, by using tools that can promote integrator debates of the foundations and practices associated with knowledges and practices of the early childhood education. Also, it brings an educational product focused on the organization of the pedagogical practice in the early childhood education, for the distance learning Pedagogy courses geared for Supervised Internships in the area composed of didactic moments indispensable for the accomplishment of the teaching practice planning.